KEBIJAKAN HUKUM PIDANA TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PORNOGRAFI - Shasri, Nadia Rachel Dwinanda; Jayakusuma, Zulfikar; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Pornography is a crime that is privacy in violation of Human Rights (HAM), especially the rights of children (right of child). Required application of criminal law policies so that the legal protection of children as victims of criminal acts of pornography can be implemented properly.This type of research used in writing this law is normative legal research that focuses on principles by formulating legal principles, both from social data and from positive written legal data. The legal principle that is used is the principle of justice regarding criminal law policies against children as victims of pornography that affects positive law in Indonesia.The results of this study are criminal law policies against children as victims of criminal acts of pornography, there must be a renewal of criminal law by applying the principle of restorative justice to children as victims of fair treatment and for perpetrators to be carried out rehabilitation of lawbreakers aimed not at retaliation. Legal protection applied to children as victims of pornography is still unable to accommodate the interests of children as victims. Legal protection given to children as victims must be able to restore the welfare of children as victims, be able to repair the damage that occurs both in terms of physical and psychological children as victims, and require the offender to contribute to the improvement by giving victims the right to receive compensation and restitution and protect it from being a victim again.Keywords: Criminal Law Policy - Children - Victims - Pornography